An Approximation Method for Solving Volterra Integrodifferential Equations with a Weighted Integral Condition - A. Guezane-Lakoud; N. Bendjazia; R. Khaldi (Journal of Function Spaces)
We apply the reproducing kernel Hilbert space (RKHS) method for getting analytical and approximate solutions for second-order hyperbolic integrodifferential equations with a weighted integral condition. The analytical solution is represented in the form of series; thus, the n-terms approximate solutions are obtained. The results of the numerical examples are compared with the exact solutions to illustrate the accuracy and the effectivity of this method.